2019
DOI: 10.1111/cen.14059
|View full text |Cite
|
Sign up to set email alerts
|

Leydig cell failure with testicular radiation doses <20Gy: The clinical effects of total body irradiation conditioned haematopoietic stem cell transplantation for childhood leukaemia during long‐term follow‐up

Abstract: Objective Testosterone replacement is generally considered likely to be required only at testicular radiation doses in excess of 20Gy. Long‐term data are not available for patients receiving 9‐14.4Gy as part of Total Body Irradiation in childhood. Design Retrospective cohort study. Data collection: notes review, laboratory results, prescription of testosterone. Patients Forty‐two of 96 boys who received Total Body Irradiation (9‐14.4Gy) and Haematopoietic Stem Cell Transplantation for childhood leukaemia at Gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…These patients differed regarding diagnosis and treatment regimens, implying a possible genetic component in the risk of Leydig cell failure, which should be addressed in future studies. Another three patients, transplanted after the onset of puberty, developed biochemical testosterone deficiency over time, lending support to Taneja et al that recently reported a substantial risk of deterioration in Leydig cell function in adulthood after pediatric HSCT (22). Taken together, these findings emphasize the need for systematic evaluation of Leydig cell function during puberty and into adulthood to allow timely treatment of testosterone deficiency.…”
Section: Discussionsupporting
confidence: 73%
“…These patients differed regarding diagnosis and treatment regimens, implying a possible genetic component in the risk of Leydig cell failure, which should be addressed in future studies. Another three patients, transplanted after the onset of puberty, developed biochemical testosterone deficiency over time, lending support to Taneja et al that recently reported a substantial risk of deterioration in Leydig cell function in adulthood after pediatric HSCT (22). Taken together, these findings emphasize the need for systematic evaluation of Leydig cell function during puberty and into adulthood to allow timely treatment of testosterone deficiency.…”
Section: Discussionsupporting
confidence: 73%
“…Several trials have reinforced the beneficial effects of testosterone therapy on muscle strength and symptoms of frailty [ 31 ]. After pediatric HSCT, gradual deterioration of Leydig cell function has been reported and a clinically significant reduction may first be detected in early adulthood [ 12 , 32 ]. Therefore, male long-term survivors of pediatric HSCT require special attention regarding symptoms of testosterone deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…When the total pelvic radiation dose is 4 Gy or more, molecular changes can occur, 60 and if the dose exceeds 20 Gy, androgen supplementation might be needed in the future. 61 In addition, TKI imatinib is said to damage Leydig cells and cause a decrease in testosterone production. 9 Besides radiation therapy to the brain, immune checkpoint inhibitors, such as nivolumab, may cause pituitary inflammation and may reduce gonadotropin secretion and subsequent testosterone production.…”
Section: Sexual Dysfunction Of Cancer Survivorsmentioning
confidence: 99%
“…Although less sensitive than germ cells, Leydig cells are also damaged by radiation. When the total pelvic radiation dose is 4 Gy or more, molecular changes can occur, 60 and if the dose exceeds 20 Gy, androgen supplementation might be needed in the future 61 . In addition, TKI imatinib is said to damage Leydig cells and cause a decrease in testosterone production 9 .…”
Section: Sexual Dysfunction Of Cancer Survivorsmentioning
confidence: 99%